The Interplay of Protein Aggregation, Genetics, and Oxidative Stress in Alzheimer's Disease: Role for Natural Antioxidants and Immunotherapeutics - Jawad Ali; Kyonghwan Choe; Jun Sung Park; Hyun Young Park; Heeyoung Kang; Tae Ju Park; Myeong Ok Kim (MDPI AG, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that comprises amyloid-beta protein (Aβ) as a main component of neuritic plaques. Its deposition is considered a trigger for AD pathogenesis, progression, and the clinical symptoms of cognitive impairment. Some distinct pathological features of AD include phosphorylation of tau protein, oxidative stress, and mitochondrial dysfunction. These pathological consequences tend to produce reactive oxygen species (ROS), resulting in the dysregulation of various signaling pathways of neuroinflammation and neurodegeneration. The relationship between the Aβ cascade and oxidative stress in AD pathogenesis is like a "chicken and egg" story, with the etiology of the disease regarding these two factors remaining a question of "which comes first." However, in this review, we have tried our best to clarify the interconnection between these two mechanisms and to show the precise cause-and-effect relationship. Based on the above hallmarks of AD, several therapeutic strategies using natural antioxidants, monoclonal antibodies, and vaccines are employed as anti-Aβ therapy to decrease ROS, Aβ burden, chronic neuroinflammation, and synaptic failure. These natural antioxidants and immunotherapeutics have demonstrated significant neuroprotective effects and symptomatic relief in various in vitro and in vivo models, as well as in clinical trials for AD. However, none of them have received final approval to enter the drug market for mitigating AD. In this review, we extensively elaborate on the pitfalls, assurances, and important crosstalk between oxidative stress and Aβ concerning current anti-Aβ therapy. Additionally, we discuss future strategies for the development of more Aβ-targeted approaches and the optimization of AD treatment and mitigation.